Conseco : market assumptions and risk - Walker, Russell, 1972- (SAGE knowledge. Cases., 2016)
In March 2007 C. James Prieur, CEO of insurance provider Conseco, was faced with a crisis. The front page of the New York Times featured a story on the grieving family of an elderly woman who had faithfully paid for her Conseco long-term care (LTC) policy, only to find that it would not pay her claims. Her family had to pay for her care (until her recent death), which unfortunately resulted in the loss of the family business. The family was now very publicly pursuing litigation. This case examines the reputational damage incurred by Conseco.